The development of cortical connections. - Price, D; Kennedy, H; Dehay, C; Zhou, L; Mercier, M; Jossin, Y; Goffinet, A; Tissir, F; Blakey, D; Molnár, Z (2006)
The cortex receives its major sensory input from the thalamus via thalamocortical axons, and cortical neurons are interconnected in complex networks by corticocortical and callosal axons. Our understanding of the mechanisms generating the circuitry that confers functional properties on cortical neurons and networks, although poor, has been advanced significantly by recent research on the molecular mechanisms of thalamocortical axonal guidance and ordering. Here we review recent advances in knowledge of how thalamocortical axons are guided and how they maintain order during that process. Several studies have shown the importance in this process of guidance molecules including Eph receptors and ephrins, members of the Wnt signalling pathway and members of a novel planar cell polarity pathway. Signalling molecules and transcription factors expressed with graded concentrations across the cortex are important in establishing cortical maps of the topography of sensory surfaces. Neural activity, both spontaneous and evoked, plays a role in refining thalamocortical connections but recent work has indicated that neural activity is less important than was previously thought for the development of some early maps. A strategy used widely in the development of corticocortical and callosal connections is the early overproduction of projections followed by selection after contact with the target structure. Here we discuss recent work in primates indicating that elimination of juvenile projections is not a major mechanism in the development of pathways feeding information forward to higher levels of cortical processing, although its use is common to developing feedback pathways.